Response of Single Bud Sprout Technique on Different Ginger (Zingiber officinale Rosc.) Cultivars under Sub-Himalayan Plains of West Bengal - Tamang, Suman; Medda, P. S.; Das, S. (International Journal of Bio-resource and Stress Management, 2022)
An experiment was carried out at Uttar Banga Krishi Vishwavidyalaya, Cooch Behar, West Bengal, during 2018−2019 and 2019−2020 to study the response of single bud sprout on six different ginger cultivars viz., Suruchi, Surabhi, Suprabha, Bhaisay, Gorubathan and a Local cultivar. Planting materials were raised from the cut pieces of rhizome weighing 5–6 g containing single bud in po-tray. Thirty-five days old planting materials of each cultivar were laid in randomized block design with four replications. Observations on growth, yield and quality parameters were recorded in the field and in laboratory following standard procedure. Results revealed a significant variation among different cultivar with regards to various attributes. The cultivar Suprabha recorded maximum number of tillers plant-1 after 180 days (5.83) after transplanting followed by Surabhi. Bhaisay recorded maximum number of leaves plant-1, plant height (50.27 cm) and produced significantly higher individual clump (145.59 g) with an average yield of 16.32 t ha-1. The cultivar Bhaisay and Suruchi recorded the maximum number of primary fingers (3.04), however maximum secondary fingers was recorded by Suruchi (6.88) followed by Bhaisay (6.12) with higher length and breadth of primary and secondary finger. With respect to quality attributes, Suprabha had higher essential oil content (2.09%), Gorubathan excelled in oleoresin content (12.25%) and lowest crude fibre content (4.42%) was recorded by Suruchi. The yield and quality of ginger raised through single bud sprout particularly with the cultivar Bhaisay and Suruchi was comparable with conventional system and found as profitable tool for large scale commercial cultivation.